A review of psychotherapy as add-on treatment to pharmacotherapy for bipolar disorder - Tay, Lay Pheng; Hassan, Siti Aishah (Medwell Journals, 2014)
Bipolar disorder is a complex illness that makes its treatment challenging. Pharmacotherapy is the foremost remedy, however not all patients benefit from medication alone. Therefore, there are increasing studies to develop various psychotherapy approaches to enhance the treatment outcome. This study presents a systematic review of literatures on the psychotherapy approaches as add-on treatment to pharmacotherapy. Among literatures relevant to psychotherapy for bipolar disorder, four common approaches have been identified as adjunct to pharmacotherapy; namely cognitive-behavioral, family-focused, interpersonal and social rhythm and psychoeducation, literatures that discussed comprehensively and structurally across these approaches with evidence-based studies were tabulated to provide a detailed view of the treatment effects for each approach. The needs for using psychotherapy in treating bipolar disorder are clarified through the factors in medication limitation, functional recovery and models of onset and relapse in the illness. Further, discussion involves treatment effects for each identified approach in every tabulated literature and differences in effectiveness relating to various aspects of the illness and treatment condition. This study concluded positively on the benefits of using the four identified psychotherapy approaches for patients with bipolar disorder. The effectiveness of each approach varies under different contexts for different aspects of the illness. Suggestions are provided for future studies.